2015
DOI: 10.5201/ipol.2015.137
|View full text |Cite
|
Sign up to set email alerts
|

A Fast C++ Implementation of Neural Network Backpropagation Training Algorithm: Application to Bayesian Optimal Image Demosaicing

Abstract: Recent years have seen a surge of interest in multilayer neural networks fueled by their successful applications in numerous image processing and computer vision tasks. In this article, we describe a C++ implementation of the stochastic gradient descent to train a multilayer neural network, where a fast and accurate acceleration of tanh(.) is achieved with linear interpolation. As an example of application, we present a neural network able to deliver state-of-the-art performance in image demosaicing. Source Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…A recently emerged trend consists in using convolutional neural networks for image processing and computer vision applications. See for example the early attempt in [19]. These methods have by now reached state-of-the-art results.…”
Section: Introductionmentioning
confidence: 99%
“…A recently emerged trend consists in using convolutional neural networks for image processing and computer vision applications. See for example the early attempt in [19]. These methods have by now reached state-of-the-art results.…”
Section: Introductionmentioning
confidence: 99%
“…We do not detail the training of our denoising neural networks as it has already been documented [7]. The only difference is that following [2], we collected the training and validation patches from Pascal VOC2012 2 and processed them according to Algorithm 1 before feeding them to the neural networks.…”
Section: Image Denoising Neural Networkmentioning
confidence: 99%
“…For example, it has been shown that a multilayer neural network, when endowed with sufficient capacity, could be trained to deliver stateof-the-art performance in denoising [2,8] as well as in demosaicing [5,9,7].…”
Section: Introductionmentioning
confidence: 99%